Versatile exclusion-based sample preparation platform for integrated rare cell isolation and analyte extraction. Issue 22 (18th October 2018) - Pezzi, Hannah M.; Guckenberger, David J.; Schehr, Jennifer L.; Rothbauer, Jacob; Stahlfeld, Charlotte; Singh, Anupama; Horn, Sacha; Schultz, Zachery D.; Bade, Rory M.; Sperger, Jamie M.; Berry, Scott M.; Lang, Joshua M.; et al.
Abstract : Automated magnetic bead sample preparation platform for positive/negative cell selection and molecular endpoints. Abstract : Rare cell populations provide a patient-centric tool to monitor disease treatment, response, and resistance. However, understanding rare cells is a complex problem, which requires cell isolation/purification and downstream molecular interrogation – processes challenged by non-target populations, which vary patient-to-patient and change with disease. As such, cell isolation platforms must be amenable to a range of sample types while maintaining high efficiency and purity. The multiplexed technology for automated extraction (mTAE) is a versatile magnetic bead-based isolation platform that facilitates positive, negative, and combinatorial selection with integrated protein staining and nucleic acid isolation. mTAE is validated by isolating circulating tumor cells (CTCs) – a model rare cell population – from breast and prostate cancer patient samples. Negative selection yielded high efficiency capture of CTCs while positive selection yielded higher purity with an average of only 95 contaminant cells captured per milliliter of processed whole blood. With combinatorial selection, an overall increase in capture efficiency was observed, highlighting the potential significance of integrating multiple capture approaches on a single platform. Following capture (and staining), on platform nucleic acid extraction enabled the detection of androgen receptor-related transcripts from CTCs isolated from prostate cancer patients. The flexibility ( e.g. negative, positive, combinatorial selection) and capabilities ( e.g. isolation, protein staining, and nucleic acid extraction) of mTAE enable users to freely interrogate specific cell populations, a capability required to understand the potential of emerging rare cell populations and readily adapt to the heterogeneity presented across clinical samples.